Preimmune Control of the Variance of TCR CDR-B3: Insights Gained From Germline Replacement of a TCR Dβ Gene Segment With an Ig DH Gene Segment - Khass, Mohamed; Levinson, Michael; Schelonka, Robert L.; Kapoor, Pratibha; Burrows, Peter D.; Schroeder, Harry W. (Frontiers in Immunology, 2020)
We have previously shown that the sequence of the immunoglobulin diversity gene segment (DH) helps dictate the structure and composition of complementarity determining region 3 of the immunoglobulin heavy chain (CDR-H3). In order to test the role of germline D sequence on the diversity of the preimmune TCRβ repertoire of T cells, we generated a mouse with a mutant TCRβ DJC locus wherein the Dβ2-Jβ2 gene segment cluster was deleted and the remaining diversity gene segment, Dβ1 (IMGT:TRDB1), was replaced with DSP2.3 (IMGT:IGHD2-02), a commonly used B cell immunoglobulin DH gene segment. Crystallographic studies have shown that the length and thus structure of TCR CDR-B3 places amino acids at the tip of CDR-B3 in a position to directly interact with peptide bound to an MHC molecule. The length distribution of complementarity determining region 3 of the T cell receptor beta chain (CDR-B3) has been proposed to be restricted largely by MHC-specific selection, disfavoring CDR-B3 that are too long or too short. Here we show that the mechanism of control of CDR-B3 length depends on the Dβ sequence, which in turn dictates exonucleolytic nibbling. By contrast, the extent of N addition and the variance of created CDR3 lengths are regulated by the cell of origin, the thymocyte. We found that the sequence of the D and control of N addition collaborate to bias the distribution of CDR-B3 lengths in the pre-immune TCR repertoire and to focus the diversity provided by N addition and the sequence of the D on that portion of CDR-B3 that is most likely to interact with the peptide that is bound to the presenting MHC.